تجديد القصيدة العباسية بين الطبع والصّنعة: دراسة نقدية مقارنة بين أبي تمام والبحتري - بوسيف عبد القادر; موساوي فرحات (University of Eloued جامعة الوادي, 2025)
تتناول هذه الورقة دراسة في بنائية القصيدة العباسية وأثرها في رسم الصّورة الشّعرية والتّجديد الذي طرأ عليها بين اتجاهي الطبع والصّنعة. وقد أثارت هذه القضية جدلا نقديا واسعا، وكان من أشهر ما أثير فيها، المقارنة بين الشّاعرين العباسيين البحتري وأبو تمام من خلال ربط الإيقاع الفنّي بالصورة، وبالمعنى الذي تتضمّنه. باستخدام منهج نقدي مقارن تأسّس على النّظر في ثلاث مكوّنات شعرية؛ الشّكل والإيقاع الفنّي للقصيدة، اللّغة والصّورة الشّعرية، المضامين والمقاصد الشّعرية، ومن خلال الانطلاق من دراسة شعر البحتري ثمّ أبو تمام، وكذلك بيان أوجه التّشابه والاختلاف، خلصت الدّراسة إلى أنّ البحتري يمثّل تيار "الطبع" الذي تميّزه السّلاسة والاعتدال، والترّكيز على الجمال الحسّي، بينما يمثّل أبو تمام تيار "الصنعة" المتّسم بالجزالة والعمق الفكري، والإغراق في البديع والمعاني العقلية. وقد أثار هذا الاختلاف جدلا نقديا، وتجديدا في القصيدة العربية العباسية. This study investigates the structure of the Abbasid poem and its effect on shaping the poetic image. It examines the innovation introduced between the natural (aṭtabaa) and crafted (aṣanaa) stylistic approaches. This issue has sparked huge critical debate, and the most prominent one was the comparison between the two Abbasid poets, Al -Buhturi and Abu Tammam, by linking artistic rhythm with imagery and the meaning it conveys. Using a comparative critical approach based on examining three poetic components; the poem’s form and artistic rhythm, the language and poetic image, the themes and poetic intentions, and by studying Al-Buhturi’s poetry followed by that of Abu Tammam, as well as identifying the similarities and differences, the study concluded that Al-Buhturi represents the “natural style” (aṭtabaa) characterized by fluidity, moderation, and sensory beauty. However, Abu Tammam represents the “crafted style” (aṣanaa), marked by grandeur, intellectual depth, and extensive use of rhetorical devices and abstract meanings. This difference sparked critical debate and innovation in the Abbasid Arabic poem.
The Innovation Of The Abbasid Poem Between Natural ‘attabaa’ And Crafted ‘asanaa’ Style: A Comparative Critical Study Of Abu Tammam And Al-buhturi
مقال . القارئ للدراسات الأدبية و النقدية و اللغوية. مج 08. ع.03.
Keywords: القصيدة العباسية، التّجديد الشّعري، الطبع والصّنعة، البحتري، أبو تمام.; Abbasid poem; poetic innovation; natural and crafted style ‘aṭtabaaʿ and ‘aṣanaa’; Al-Buhturi; Abu Tammam